The Economics and Econometrics of Gene-Environment Interplay - Pietro Biroli; Titus Galama; Stephanie von Hinke; Hans van Kippersluis; Cornelius A. Rietveld; Kevin Thom (Tinbergen Institute, 2022)
Economists and social scientists have debated the relative importance of nature (one's genes) and nurture (one's environment) for decades, if not centuries. This debate can now be informed by the ready availability of genetic data in a growing number of social science datasets. This paper explores the potential uses of genetic data in economics, with a focus on estimating the interplay between nature (genes) and nurture (environment). We discuss how economists can benefit from incorporating genetic data into their analyses even when they do not have a direct interest in estimating genetic effects. We argue that gene-environment (G E) studies can be instrumental for (i) testing economic theory, (ii) uncovering economic or behavioral mechanisms, and (iii) analyzing treatment effect heterogeneity, thereby improving the understanding of how (policy) interventions affect population subgroups. We introduce the reader to essential genetic terminology, develop a conceptual economic model to interpret gene-environment interplay, and provide practical guidance to empirical researchers.
Keywords: D1; D3; I1; I2; J1; 330; Gene-by-Environment Interplay; Polygenic Indices; Social Science Genetics ALSPAC